2014
DOI: 10.1021/nn500193y
|View full text |Cite
|
Sign up to set email alerts
|

Crafting Threads of Diblock Copolymer Micelles via Flow-Enabled Self-Assembly

Abstract: Hierarchically assembled amphiphilic diblock copolymer micelles were exquisitely crafted over large areas by capitalizing on two concurrent self-assembling processes at different length scales, namely, the periodic threads composed of a monolayer or a bilayer of diblock copolymer micelles precisely positioned by flow-enabled self-assembly (FESA) on the microscopic scale and the self-assembly of amphiphilic diblock copolymer micelles into ordered arrays within an individual thread on the nanometer scale. A mini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
71
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 40 publications
0
71
0
Order By: Relevance
“…Oppositely, two kinds of higher surface tension solvents like carbon disulde (CS 2 ) and chlorobenzene (CB) were chosen to compare. 20 These results showed that the surface tension inuenced the formation of the stripes and higher surface tension was not benecial to the stripes formation in the capillary tubes. 5a and b), while in CB solution of P3HT, similar to the P3HT in CF solution, 30 but few ngering instability, nearly continuous and irregular line were formed (Fig.…”
Section: Surface Tension Effects On the Self-assembly Of P3htmentioning
confidence: 89%
See 1 more Smart Citation
“…Oppositely, two kinds of higher surface tension solvents like carbon disulde (CS 2 ) and chlorobenzene (CB) were chosen to compare. 20 These results showed that the surface tension inuenced the formation of the stripes and higher surface tension was not benecial to the stripes formation in the capillary tubes. 5a and b), while in CB solution of P3HT, similar to the P3HT in CF solution, 30 but few ngering instability, nearly continuous and irregular line were formed (Fig.…”
Section: Surface Tension Effects On the Self-assembly Of P3htmentioning
confidence: 89%
“…14 For instance, the use of supramolecular self-assembly methods, 15 LB lm deposition technology 16 and self-assembly methods based on evaporation like controlled evaporative self-assembly (CESA). 19,20 Among them, CESA is a simple, rapid, economical method with good controllability and has access to a rich and large-area varied topography. 19,20 Among them, CESA is a simple, rapid, economical method with good controllability and has access to a rich and large-area varied topography.…”
Section: Introductionmentioning
confidence: 99%
“…The miscibility of the metal salt in the selective solvent need not be favorable. [188] There have been numerous metal nanoparticles (e.g., Au, Co, Ni, Pb, and Cu [189] ) generated from SABCMs (Figure 8b). [172] The other block is usually PS(polystyrene), which is incompatible with the P4VP/P2VP block.…”
Section: Self-assembled Block Copolymer Micellesmentioning
confidence: 99%
“…[24,25] In this context, tetra chloroauric acid (HAuCl 4 ·xH 2 O) was used as gold precursors which can preferentially be incorporated into the P4VP cores via ionic-polar interactions. [24,25] In this context, tetra chloroauric acid (HAuCl 4 ·xH 2 O) was used as gold precursors which can preferentially be incorporated into the P4VP cores via ionic-polar interactions.…”
Section: Doi: 101002/marc201900525mentioning
confidence: 99%